-3+7x(2)=6-14x

Simple and best practice solution for -3+7x(2)=6-14x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3+7x(2)=6-14x equation:



-3+7x(2)=6-14x
We move all terms to the left:
-3+7x(2)-(6-14x)=0
We add all the numbers together, and all the variables
7x2-(-14x+6)-3=0
We add all the numbers together, and all the variables
7x^2-(-14x+6)-3=0
We get rid of parentheses
7x^2+14x-6-3=0
We add all the numbers together, and all the variables
7x^2+14x-9=0
a = 7; b = 14; c = -9;
Δ = b2-4ac
Δ = 142-4·7·(-9)
Δ = 448
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:
$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}$
$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}$

The end solution:
$\sqrt{\Delta}=\sqrt{448}=\sqrt{64*7}=\sqrt{64}*\sqrt{7}=8\sqrt{7}$
$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(14)-8\sqrt{7}}{2*7}=\frac{-14-8\sqrt{7}}{14} $
$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(14)+8\sqrt{7}}{2*7}=\frac{-14+8\sqrt{7}}{14} $

See similar equations:

| −4(5n−7)=10n−2 | | 12-u=166 | | 2x-4=(7x-14)/(x+2) | | 6x-12=4x+28 | | 9+x+2x=60 | | 9u+1=26 | | 6x-12=3x/2 | | 9.4q-4.1=13.5q | | 6x+25=14x+47 | | 3y=2.2y+3.2 | | -0.9=0.6+m/11 | | 12g-2=14g-6 | | 16x-8-16x=0 | | 5.1z-9.4=11 | | -20.4=u/6-1.2 | | 3(5x+1)+2(1-6x=9 | | z/5=3/10=+7 | | (-x)-17=(-63) | | -4.2-16r=-12.2 | | 4(2x+1)=6(x+2 | | -4.6=1.4+0.3u | | -39=-5u+2(u-6) | | b/0.2-12=-6.5 | | 8x-21=3(x-7)+6x | | 4z-59=77 | | -18x-19=-91 | | 2x−x=11 | | 14(3r+4)-18r=8 | | 6r−4r=12 | | F(r)=3.14r2 | | 14+7y-3y=26 | | 18j−17j=12 |

Equations solver categories